Quantification of plant dispersal ability within and beyond a calcareous grassland. (15th December 2012) - Diacon‐Bolli, Jacqueline C.; Edwards, Peter J.; Bugmann, Harald; Scheidegger, Christoph; Wagner, Helene H.; Cousins, Sara
Abstract Question Many calcareous grasslands in Europe have declined in species richness in recent decades. This loss of species could be partly due to habitat loss and fragmentation, leading to increased distances and reduced connectivity through seed flow between calcareous grassland patches resulting in increased local extinction risk related to small population size, and partly due to abandonment of traditional management practices that fostered dispersal within and between patches. Here, we quantify short‐ and intermediate‐distance dispersal ability of dry calcareous grassland species and relate these to dispersal traits. Location Schaffhauser Randen, Switzerland. Methods We studied wind dispersal of diaspores under natural conditions within and beyond two replicate calcareous grassland patches. Funnel traps (n = 230) were set up at heights of 0.2 m and 0.7 m along ten transects traversing the calcareous grassland and extending 40 m into the surrounding landscape. We developed a new method for quantifying short ‐ (0–1 m) and intermediate‐distance (1–40 m) dispersal ability, related these to species traits, and tested whether they were able to explain dispersal rates into the adjacent landscape. Results While grasses could be categorized as good dispersers over short or intermediate distances, or both, forbs were generally poor dispersers over both distance classes. Only small numbers of diaspores were found in the adjacent landscape, and these were predominantly grasses. Diaspore traits, such as terminal velocity or diaspore mass, contributed little to explaining dispersal ability, whereas release height was an important predictor, especially for intermediate‐distance dispersal. Conclusions Under natural field conditions, dispersal into the adjacent landscape depends on release height rather than terminal velocity, and is heavily biased towards grasses, so that seed rain does not reflect the species composition of the calcareous grassland community. Thus natural regeneration of species richness of degenerated calcareous grassland communities even over short distances should not rely on wind dispersal alone.